CFD simulation of heat transfer in shell and tube heat exchanger - Khairun Hasmadi, Othman (2009)
Computational Fluid Dynamic (CFD) is a useful tool in solving and analyzing problems that involve fluid flows, while shell and tube heat exchanger is the most common type of heat exchanger and widely use in oil refinery and other large chemical processes because it suite for high pressure application. The processes in solving the simulation consist of modeling and meshing the basic geometry of shell and tube heat exchanger using the CFD package Gambit 2.4. Then, the boundary condition will be set before been simulate in Fluent 6.2 based on the experimental parameters. Parameter that had been used was the same parameter of experimental at constant mass flow rate of cold water and varies with mass flow rate at 0.0151 kg/s, 0.0161 kg/s and 0.0168 kg/s of hot water. Thus, this paper presents the simulation of heat transfer in shell and tube heat exchanger model and validation to heat transfer in Shell and Tube Heat Exchanger Studies Unit (Model HE 667) that been used in UMP’s chemical engineering laboratory. The CFD model is validated by comparison to the experimental results within 15% error.